A survey of twin‐row cropping systems in North Carolina. Issue 1 (28th June 2021) - Tilley, M. Scott; Jordan, David L.; Heiniger, Ronnie W.; Vann, Rachel; Crozier, Carl R.; Gatiboni, Luke
Abstract: Twin‐row (TR) cropping systems have maintained a presence in North Carolina (NC) for more than 30 years. Introduced as an alternative to the single‐row (SR) configuration, it is hypothesized individual plants arranged 7‐ to 9‐inches apart see a decrease in plant‐to‐plant competition. However, the success of TR remains elusive. Only a handful of farmers across NC have been able to increase yield through the implementation of TR. As higher yields are achieved in research using SR, the use of TR is becoming less attractive to growers looking to modernize. In order to understand future trends, two surveys were administered across the state of NC with the following objectives: (a) identify standard production practices used such as row spacing, TR spacing, starter fertilizer placement, and layby application methods, (b) evaluate grower testimonies concerning observed plant stress under diverse environmental conditions, and (c) identify the successes and limitations observed with TR production. Of the 461 farmers surveyed in the general survey, 42% stated they are planting on narrow (30 inch or less) SR with 58% still planting on 36‐inch or greater row spacing. Within the 58%, 148 farmers stated they are considering a transition from wide (>30 inches) to narrow row systems. One hundred and twenty farmers said they would remain on wide SR. In time, 74% of growers will potentially be planting on narrow rows. Twenty‐eight TR farmers (6%) were identified. Two of the 28 twin‐row growers stated they would be reverting back to single‐row production. Core Ideas: The success of twin‐row cropping systems remains elusive. Farmers growing twin‐row are reverting back to single‐row production. Single‐row centers <36 inches will become the dominant row spacing in grain crops.